Enhanced Specialized Transduction Using Recombineering in Mycobacterium tuberculosis - JoAnn M. Tufariello (American Society for Microbiology, 2014)
ABSTRACT Genetic engineering has contributed greatly to our understanding of Mycobacterium tuberculosis biology and has facilitated antimycobacterial and vaccine development. However, methods to generate M. tuberculosis deletion mutants remain labor-intensive and relatively inefficient. Here, methods are described that significantly enhance the efficiency (greater than 100-fold) of recovering deletion mutants by the expression of mycobacteriophage recombineering functions during the course of infection with specialized transducing phages delivering allelic exchange substrates. This system has been successfully applied to the CDC1551 strain of M. tuberculosis, as well as to a ΔrecD mutant generated in the CDC1551 parental strain. The latter studies were undertaken as there were precedents in both the Escherichia coli literature and mycobacterial literature for enhancement of homologous recombination in strains lacking RecD. In combination, these measures yielded a dramatic increase in the recovery of deletion mutants and are expected to facilitate construction of a comprehensive library of mutants with every nonessential gene of M. tuberculosis deleted. The findings also open up the potential for sophisticated genetic screens, such as synthetic lethal analyses, which have so far not been feasible for the slow-growing mycobacteria. IMPORTANCE Genetic manipulation of M. tuberculosis is hampered by laborious and relatively inefficient methods for generating deletion mutant strains. The combined use of phage-based transduction and recombineering methods greatly enhances the efficiency by which knockout strains can be generated. The additional elimination of recD further enhances this efficiency. The methods described herein will facilitate the construction of comprehensive gene knockout libraries and expedite the isolation of previously difficult to recover mutants, promoting antimicrobial and vaccine development.